(untitled) (Swiss Medical Weekly, 2020)
Acute and recurrent urinary tract infections (UTIs) are common auto-infectious diseases transmitted from the intestinal tract. They affect the urinary tract either through recurrence or through persistence. The incidence of UTIs increases with age and comorbidities. In this guideline from the Swiss Society of Gynaecology and Obstetrics (SSGO), diagnosis and treatment of UTIs are grouped into uncomplicated and complicated cases. This is to our knowledge the first guideline that specifically considers UTIs in pregnancy and breastfeeding, and the prevention of UTIs in the context of urogynaecological diagnosis and surgery. Recommendations are based on observational, retrospective or randomised controlled studies. The level of evidence was rated according to recommendations made by the Oxford Centre of Evidence-based Medicine. In non-pregnant women and women <65 years with dysuria, pollakiuria and suprapubic pain, no urine diagnostic testing is needed. If the clinical presentation is unclear, urinary tests such as midstream urine stix or urine analysis should be used, and in cases of unclear or recurrent infections, a urine culture. Routine screening for asymptomatic bacteriuria (ASB) should not be carried out, and antibiotic treatment should be avoided in cases of incidentally detected ASB. As an exception, screening for bacteriuria should be carried out in patients prior to urogynaecological surgery where urinary drainage by catheter is necessary or probable. In pregnancy, systematic screening for ASB is not recommended, because most women with ASB do not develop complications during follow-up, and contamination of urine samples collected in pregnancy is common. Patients should be advised that most UTIs are self-limiting, that the symptoms can be relieved with non-steroidal anti-inflammatory drugs (NSAIDs) and that the same time is required to eradicate the bacteria using antibiotics or NSAIDs. For non-pregnant women with uncomplicated UTIs, a 48-hour-delayed antibiotic prescription is recommended, supplemented by NSAIDs for pain relief. If antibiotics are needed after 48 hours, or in case of direct antibiotic administration in pregnant women, the shortest possible course of treatment should be carried out. There is increasing interest in alternatives or complementary treatments to antibiotic therapy, especially for recurrent UTIs. Different recommendations and alternative medications are summarised. This short and comprehensive guideline provides quick answers for every day clinical questions concerning UTIs, especially for obstetricians and gynaecologists.